Uganda: elephants, people and fire in Murchison Falls National Park and north Bunyoro district - Ian Parker (Pachyderm)
This is an historical essay on the environmental changes mediated by elephants, people and fire in Uganda’s Murchison Falls National Park and Bunyoro District from before the colonial era to the present. It draws heavily on Thomas and Scott (1935) and on Laws, Parker and Johnstone’s Uganda work up to 1970 and unpublished observations thereafter. In the space of a century, areas of woodland and forest changed to open, treeless grassland, back to woodland, and finally to treeless farmland. These changes were brought about by elephants and people both interacting and independently, to which fire while exerting profound secondary influences on the biota, was ancillary. In Bunyoro elephants replaced people and people in turn replaced elephants, in the processes reducing the diversity of life about them. Against the received wisdom of the times that forest and woodland recovery is slow, there is evidence on how fast their physiography if not the specific components, can re-appear.